1970
DOI: 10.3126/hren.v8i2.4426
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Profile of Multiple Myeloma in the Patients Visiting BPKIHS as Diagnosed by Agarose Gel Electrophoresis

Abstract: Multiple myeloma is a proliferative disease of plasma cells. The incidence of the disease increases with age. Objectives : To study different biochemical parameters and serum agarose gel electrophoresis patterns of patients consistent with clinical symptoms of multiple myeloma. Subject and Methods : A retrospective study was carried out in Department of Biochemistry, B.P. Koirala Institute of Health Sciences, from October 2008 to September 2009. Patients consistent with the symptoms of multiple myeloma were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
2
0
0
Order By: Relevance
“…As a result, a high concentration of monoclonal antibodies is present in bone marrow as well as in serum. 45 Highly significant increase in serum levels of IgG was observed in MM patients in this study; this is similar to the results reported by another study. 45 Similar results have been observed by Harousseau and Dreyling, they noticed that in most cases of multiple myeloma, there is a malignant proliferation of plasma cells producing IgG.…”
Section: Frequency Of M Bands Showed By Serum Protein Electrophoresissupporting
confidence: 82%
See 1 more Smart Citation
“…As a result, a high concentration of monoclonal antibodies is present in bone marrow as well as in serum. 45 Highly significant increase in serum levels of IgG was observed in MM patients in this study; this is similar to the results reported by another study. 45 Similar results have been observed by Harousseau and Dreyling, they noticed that in most cases of multiple myeloma, there is a malignant proliferation of plasma cells producing IgG.…”
Section: Frequency Of M Bands Showed By Serum Protein Electrophoresissupporting
confidence: 82%
“…45 Highly significant increase in serum levels of IgG was observed in MM patients in this study; this is similar to the results reported by another study. 45 Similar results have been observed by Harousseau and Dreyling, they noticed that in most cases of multiple myeloma, there is a malignant proliferation of plasma cells producing IgG. 46 Even though the mean IgG level was higher than other immunoglobulin classes in our study, it was still in the normal range this one in concordance with other previous study which was done by another study.…”
Section: Frequency Of M Bands Showed By Serum Protein Electrophoresissupporting
confidence: 82%